Exploring Innovations and Key Insights in Healthcare - Cortes, Arthur R. G.; Henriques, Bruno; Sarmento, Bruno; Rodrigues, Célia Fortuna; Souza, Júlio C. M.; Tiritan, Maria Elizabeth; Brito, Nuno Vieira; Cass, Quezia Bezerra; Dinis-Oliveira, Ricardo Jorge; Warnakulasuriya, Saman; Bolanos-Garcia, Victor M.; Bousbaa, Hassan (Scientific Letters, 2025)
On behalf of the Editorial Team of Scientific Letters, we are pleased to announce the publication of the third issue. The 2024 edition of Scientific Letters presents a diverse array of research that highlights significant advancements in health, dentistry, and clinical treatments.